Factors associated with COVID-19 stigma during the onset of the global pandemic in India: A cross-sectional study - Adhikari, Tulsi; Aggarwal, Sumit; Nair, Saritha; Joshi, Aparna; Diwan, Vishal; Stephen, A.; Devi, K. Rekha; Kumar Mishra, Bijaya; Yadav, Girijesh Kumar; Bangar, Sampada Dipak; Sahu, Damodar; Yadav, Jeetendra; et al. (Frontiers in Public Health, 2022)
Objective To assess factors associated with COVID-19 stigmatizing attitudes in the community and stigma experiences of COVID-19 recovered individuals during first wave of COVID-19 pandemic in India. Methods A cross-sectional study was conducted in 18 districts located in 7 States in India during September 2020 to January 2021 among adults > 18 years of age selected through systematic random sampling. Data on socio demographic and COVID-19 knowledge were collected from 303 COVID-19 recovered and 1,976 non-COVID-19 infected individuals from community using a survey questionnaire. Stigma was assessed using COVID-19 Stigma Scale and Community COVID-19 Stigma Scale developed for the study. Informed consent was sought from the participants. Univariate and multivariate binary logistic regression analysis were conducted. Results Half of the participants (51.3%) from the community reported prevalence of severe stigmatizing attitudes toward COVID-19 infected while 38.6% of COVID-19 recovered participants reported experiencing severe stigma. Participants from the community were more likely to report stigmatizing attitudes toward COVID-19 infected if they were residents of high prevalent COVID-19 zone (AOR: 1.5; CI: 1.2–1.9), staying in rural areas (AOR: 1.5; CI:1.1–1.9), belonged to the age group of 18–30 years (AOR: 1.6; CI 1.2–2.0), were male (AOR: 1.6; CI: 1.3–1.9), illiterate (AOR: 2.7; CI: 1.8–4.2), or living in Maharashtra (AOR: 7.4; CI: 4.8–11.3). COVID-19 recovered participants had higher odds of experiencing stigma if they had poor knowledge about COVID-19 transmission (AOR: 2.8; CI: 1.3–6.3), were staying for 6–15 years (AOR: 3.24; CI: 1.1–9.4) in the current place of residence or belonged to Delhi (AOR: 5.3; CI: 1.04–26.7). Conclusion Findings indicated presence of stigmatizing attitudes in the community as well as experienced stigma among COVID-19 recovered across selected study sites in India during the first wave of COVID-19 pandemic. Study recommends timely dissemination of factual information to populations vulnerable to misinformation and psychosocial interventions for individuals affected by stigma.